Smart specialization: a spontaneous four-step process in the mixed Arab–Jewish region of Haifa and Nazareth. Issue 5 (4th May 2022) - Shilon, Mor; Kaufmann, Dan; Schwartz, Dafna; Rosiello, Alessandro
ABSTRACT: Smart specialization is studied in the Arab–Jewish region of Haifa and Nazareth, with a focus on high-tech ventures created by Arab entrepreneurs. We find that not only did smart specialization occur under these complex conditions, but also it was spontaneous. It began with the sharing of entrepreneurial knowledge held by Jewish entrepreneurs through social networks set up by grassroots organizations. Policy initiatives in support of this process followed, helping to reshape the region's socioeconomic structure. Therefore, we argue that smart specialization followed a four-phase process: a pre-phase of knowledge transfer between the two communities, followed by Foray's three phases .